Purification of tawhid in Islam through the Quran and Hadith - Azwira Abdul Aziz,; Aminudin Basir@Ahmad,; Hazman Hassan,; Sakinah Saptu, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This article introduces the concept of tawhid’s purification as the methodology of prophets in calling to Allah, embedded in the revelation. In order to define Islamic epistemology through the study of Qur’anic and Hadith texts as well as to glorify both as the sacred source of thought, an analytical study of selected 24 Qur’anic verses and 48 authentic hadiths has been used. Through the combination of traditional and digital method, the number of selected Qur’anic verses and authentic hadiths is considered adequate to prove the existence of tawhid purification in revealed texts as the core foundation of Islamic epistemology. From the 72 texts on tawhid purification analyzed, 7 Qur’anic verses and 19 hadiths focussed on tawhid purification in belief; 16 Qur’anic verses and 18 hadiths focuseds on physical acts of worship, while the rest consisting one Qur’anic verse with 11 hadiths highlighted the verbal acts of worship. This study has verified that the concept of tawhid purification is not a new ideology created by certain groups. On the contrary, the revealed texts of Qur’an and hadith has manifested the concept of tawhid purification since the earliest days of Islam through the call of many prophets to Allah.Therefore concerted efforts should be taken to educate the Islamic society in understanding tawhid purification as the key methodology of prophets in calling to Allah and as confirmed by the revelation. Thus, negative perceptions viewing it as the ideology of extremists should be properly regulated.